COMMUNICATION STRATEGY PRIVATE COLLEGE IN INCREASE BRAND EQUITY - Agus Kristian (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2022)
This study examines brand and communication strategies undertaken by Muhammadiyah University of Tangerang in building brand equity. The purpose of research to know and evaluate brand and communication strategy in building brand equity of Muhammadiyah University of Tangerang dissemination of competition of private universities in increasing number of new students. Theoretical basis of research is the theory of brand equity. The paradigm in this research is constructivist paradigm, using qualitative approach and through case study method to look for its specificity. Primary data were obtained from key informants through interviews and observation. While secondary data obtained through document studies. Data were analyzed qualitatively using brand equity elements as well as withdrawal of conclusions or verifications. To check the validity of data is done by tringulasi sources and methods and discuss with colleagues. The results showed that: First, the factor of formation of brand equity of Muhammadiyah University of Tangerang include: (1). 1) Institutional and Study Accreditation, 2) Achievements, 3) Campaign Superior Activities, 4) Premium Cost, 5) Shif Class, and 6) Relationship with Alumni.